Clumped isotope composition of cold-water corals: A role for vital effects? - Peter T. Spooner; Weifu Guo; Laura F. Robinson; Nivedita Thiagarajan; Katharine R. Hendry; Brad E. Rosenheim; Melanie J. Leng (Geochimica et Cosmochimica Acta, 2016)
Abstract The carbonate clumped isotope thermometer is a promising tool for determining past ocean temperatures. It is based on the temperature dependence of rare isotopes ‘clumping’ into the same carbonate ion group in the carbonate mineral lattice. The extent of this clumping effect is independent of the isotope composition of the water from which carbonate precipitates, providing unique advantages over many other paleotemperature proxies. Existing calibrations of this thermometer in cold-water and warm-water corals suggest clumped isotope ‘vital effects’ are negligible in cold-water corals but may be significant in warm-water corals. Here, we test the calibration of the carbonate clumped isotope thermometer in cold-water corals with a recently collected and well characterised sample set spanning a range of coral genera (Balanophyllia, Caryophyllia, Dasmosmilia, Desmophyllum, Enallopsammia and Javania). The clumped isotope compositions (Δ47) of these corals exhibit systematic dependences on their growth temperatures, confirming the basis of the carbonate clumped isotope thermometer. However, some cold-water coral genera show Δ47 values that are higher than the expected equilibrium values by up to 0.05‰ (equivalent to underestimating temperature by ∼9 °C) similar to previous findings for some warm-water corals. This finding suggests that the vital effects affecting corals Δ47 are common to both warm- and cold-water corals. By comparison with models of the coral calcification process we suggest that the clumped isotope offsets in these genera are related to the kinetic isotope effects associated with \{CO2\} hydration/hydroxylation reactions in the corals’ calcifying fluid. Our findings complicate the use of the carbonate clumped isotope thermometer in corals, but suggest that species- or genus-specific calibrations could be useful for the future application of this paleotemperature proxy.